Investigate the indoor air quality in store room - Harivin Raj A /l Mohan (2023)
This thesis presents a study on Indoor Air Quality (IAQ) of store rooms in administration building. This study was conducted to determine and analyse the IAQ parameters in respected store rooms. The IAQ parameter assessed in this study are temperature, air velocity, relative humidity, carbon dioxide (CO₂) and particulates (PM₁₀). The samplings were taken three times in a day by using several measurements instrument which are particle counter model CEM DT-9883M and anemometer model LM-8000. Average reading of IAQ parameters were analysed with the acceptable range and limit provided by Department of Occupational Safety and Health (DOSH) in Industry Code of Practice on Indoor Air Quality. The analysed data shows that, second floor store room has good indoor air quality and basement store room has higher level of relative humidity than acceptable maximum range. It is due to the water leakage problem in basement floor and improper ventilation system. Recommendations to improve the IAQ of store rooms was also presented in this study. By eliminating the identified source of contamination, the IAQ of store rooms can be improved. Implementations like removal of contaminated building products and installation of filtration system in mechanical ventilation can improve the air quality of indoor space